2021
DOI: 10.1007/s10654-021-00728-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine acceptance among pregnant women and mothers of young children: results of a survey in 16 countries

Abstract: With the development of multiple effective vaccines, reducing the global morbidity and mortality of COVID-19 will depend on the distribution and acceptance of COVID-19 vaccination. Estimates of global vaccine acceptance among pregnant women and mothers of young children are yet unknown. An understanding of the challenges and correlates to vaccine acceptance will aid the acceleration of vaccine administration within these populations. Acceptance of COVID-19 vaccination among pregnant women and mothers of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

71
583
16
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(678 citation statements)
references
References 19 publications
71
583
16
8
Order By: Relevance
“…For breastfeeding women, the observed likelihood of getting a vaccine whilst breastfeeding (59%) is quite similar to estimates measured within the general public in European (68%) and American samples (62%) at that time [29,32]. However, COVID-19 vaccine willingness during pregnancy, as measured in our sample (49% if excluding Belgian data), is lower than observed in the other samples at that time (62-68%) [29,32], but in line with estimates calculated among an international cohort of pregnant women in October-November 2020 (52%) [33]. Thus, our findings do not only demonstrate that COVID-19 "vaccine hesitancy" is also prevalent in the perinatal population, but that it might occur even more often in pregnancy.…”
Section: Main Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…For breastfeeding women, the observed likelihood of getting a vaccine whilst breastfeeding (59%) is quite similar to estimates measured within the general public in European (68%) and American samples (62%) at that time [29,32]. However, COVID-19 vaccine willingness during pregnancy, as measured in our sample (49% if excluding Belgian data), is lower than observed in the other samples at that time (62-68%) [29,32], but in line with estimates calculated among an international cohort of pregnant women in October-November 2020 (52%) [33]. Thus, our findings do not only demonstrate that COVID-19 "vaccine hesitancy" is also prevalent in the perinatal population, but that it might occur even more often in pregnancy.…”
Section: Main Findingssupporting
confidence: 89%
“…Overall, about 60-70% of the women indicated that they were willing to get a COVID-19 vaccine during pregnancy or breastfeeding; all countries had a larger proportion of breastfeeding women in favor of the vaccine. However, and as previously shown [32,33], substantial differences were observed across countries (range: 30-80%), and even between communities within the same country (Belgium, range: 49-82%). Differences between countries may be, at least partially, explained by the different timing of study execution and consequently by the different stage of the pandemic with different incidence rates of COVID-19 cases and containment measures in place at the time of survey completion (Belgium = April-May 2020, i.e., at the peak of the first wave of the pandemic when a strict lockdown was still in effect; other countries = June-July 2020, i.e., at the end of the first wave of the pandemic in most countries, except the UK, when restrictions were mostly lifted) (see Supplementary Material Table S8 and Figure S3) [31].…”
Section: Main Findingssupporting
confidence: 79%
“…Of notable importance, over 70% of the respondents in our survey reported a positive attitude to get COVID-19 vaccination for themselves, their spouses and children. This vaccination willingness was much higher than those among parents in England (55.8% for themselves and 48.2% for children) ( Bell et al, 2020 ), Turkey (33.9%-62.6% for themselves, 28.9%-56.8% for children) ( Yigit et al, 2021 ), Kuwait (44.2% for children) ( AlHajri et al, 2021 ), and multinational surveys (65.0%-69.2%for children) ( Goldman et al, 2020 ; Skjefte et al, 2021 ), but lower than that in Italy (over 90% for children) ( Pierantoni et al, 2021 ). Despite the difference of study sites, the willingness to vaccinate children in our survey were in line with a previous survey among factory workers in Shenzhen (72.6%) ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 74%
“…This suggests that particularly young children are considered to be more sensitive to possible side effects of vaccination. Other studies focused on the quality of the approval process for a COVID-19 vaccine for children: While Skjefte et al found that a major reason for mothers’ refusal of a COVID-19 vaccination for their child was concerns about insufficient data collection during the approval process [ 12 ], an international survey revealed that more than 40% of parents would accept even shortcuts in order to fasten the approval process for children [ 5 ]. In any case, once a COVID-19 vaccine will have been approved for children, special emphasis will be needed to convince parents that it is safe to have their child vaccinated.…”
Section: Discussionmentioning
confidence: 99%